Ovariectomy-induced reductions in endothelial SK3 channel activity and endothelium-dependent vasorelaxation in murine mesenteric arteries. - Fui C Yap; Mark S Taylor; Mike T Lin (PLoS ONE, 2014)
Mesenteric artery endothelium expresses both small (SK3)- and intermediate (IK1)-conductance Ca(2+)-activated K(+) (KCa) channels whose activity modulates vascular tone via endothelium-dependent hyperpolarization (EDH). Two other major endothelium-dependent vasodilation pathways utilize nitric oxide (NO) and prostacyclin (PGI2). To examine how ovariectomy (ovx) affects the basal activity and acetylcholine (ACh)-induced activity of each of these three pathways to vasorelaxation, we used wire myograph and electrophysiological recordings. The results from functional studies using isolated murine mesenteric arteries show that ovx reduces ACh-induced endothelium-dependent vasodilation due to decreased EDH and NO contributions, although the contribution of PGI2 is upregulated. Both endothelial SK3 and IK1 channels are functionally coupled to TRPV4 (transient receptor potential, vanilloid type 4) channels: the activation of TRPV4 channels activates SK3 and IK1 channels, leading to EDH-mediated vascular relaxation. The decreased EDH-mediated vasorelaxation in ovx vessels is due to reduced SK3 channel contribution to the pathway. Further, whole-cell recordings using dispersed endothelial cells also show reduced SK3 current density in ovx endothelial cells. Consequently, activation of TRPV4 channels induces smaller changes in whole-cell current density. Thus, ovariectomy leads to a reduction in endothelial SK3 channel activity thereby reducing the SK3 contribution to EDH vasorelaxation.